Artificial Bee Colony for Solving Multi-Objectives Three-Dimensional Knapsack Problem - Suriya Phongmoo (2020)
© 2020 ACM. The objectives of this research aim to apply the mathematical model, to propose an Artificial Bee Colony for Solving Three-Dimensional Knapsack Problem and to determine the optimal parameters of an Artificial Bee Colony Algorithm. This work application of heuristic approach is used for optimizing containers loading problem and we has a contract with logistic and transport company in the northern of Thailand to joint on this research. For the containers loading problem are the Three-Dimensional Knapsack Problem and it will be solving the real problem within the supporting of logistic and transport company in the northern of Thailand. However we deal with Nim See Seng Transport 1988 Co., Ltd cause of they are the big transportation company in the north of Thailand. The result of this research will be comparing between performance of the result in OR-Library which is a database that collects the best optimal solution data about Three-Dimensional Knapsack Problem and Artificial Bee Colony Algorithm, on the other hand Artificial Bee Colony Algorithm will be provides the good solutions within the satisfaction computer runtime, maximize profit, minimize empty space and respond to customers satisfaction also.